The personalization–privacy paradox at the nexus of social exchange and construal level theories. Issue 3 (26th August 2021) - Cloarec, Julien; Meyer‐Waarden, Lars; Munzel, Andreas
Abstract: Marketing personalization requires firms to collect information that they can use to personalize their products or services, which might raise consumer privacy concerns. Prior studies on construal level theory suggest that happier Internet users would likely take future rewards in social exchanges (e.g., personalization–privacy trade‐offs) into greater consideration. Building on both social exchange and construal level theories, this article investigates the extent to which happiness with the Internet drives the personalization–privacy paradox, as well as the moderating role of experience sharing frequency as a proxy for reciprocity. An online survey administered to a representative sample of French consumers ( n  = 649) largely confirms the predictions. Happiness with the Internet is the strongest driver of willingness to disclose information in exchange for personalization, surpassing conventional privacy‐related constructs (e.g., trust and risk beliefs). In line with social exchange theory, reciprocity has an important influence on online social exchanges too.